2003
DOI: 10.1088/0953-8984/15/4/311
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Prin SrAl12O19under vacuum ultraviolet synchrotron excitation

Abstract: SrAl12O19:Pr phosphors have been investigated under ultraviolet/vacuum ultraviolet (5–20 eV) synchrotron radiation at room and near liquid He temperatures. The excitation of 1S 0 →1I 6 and 3P 0 →3H 4 emission of Pr3+ in SrAl12O19 occurs in a 1 eV wide region originating from the interconfiguration 4f2 → 4f5d transitions with threshold (onset of the transitions) at 6.0 eV at room temperature and at 6.15 eV at 14 K. A comparison of the excitation spectra of Pr3+ and known data for Ce3+ in SrAl12O19 reveals a shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Such excitation transitions in Pr 3+ doped strontium compounds have been reported [8,9]. It has also been reported that 486 nm transition in Pr 3+ is between 3 P 0 to 3 H 4 [8] and above 600 nm transition between 1 D 2 -3 H 4 and 3 P 0 -3 H 6, 3 F J states [3,[8][9][10]. When electrons are excited to 3 P 0,1,2 levels, they may either relax to 3 P 0 state and recombine to 3 happening through such substitution and vacancy centres.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Such excitation transitions in Pr 3+ doped strontium compounds have been reported [8,9]. It has also been reported that 486 nm transition in Pr 3+ is between 3 P 0 to 3 H 4 [8] and above 600 nm transition between 1 D 2 -3 H 4 and 3 P 0 -3 H 6, 3 F J states [3,[8][9][10]. When electrons are excited to 3 P 0,1,2 levels, they may either relax to 3 P 0 state and recombine to 3 happening through such substitution and vacancy centres.…”
Section: Resultsmentioning
confidence: 65%
“…PL excitation at 440, 460 and 480 nm are due to excitation from 3 H 4 ground state to 3 P 0,1,2 excited state in the 4f 2 configuration of Pr 3+ , situated intragap in SrAl 2 O 4 . Such excitation transitions in Pr 3+ doped strontium compounds have been reported [8,9]. It has also been reported that 486 nm transition in Pr 3+ is between 3 P 0 to 3 H 4 [8] and above 600 nm transition between 1 D 2 -3 H 4 and 3 P 0 -3 H 6, 3 F J states [3,[8][9][10].…”
Section: Resultsmentioning
confidence: 78%
“…This paper has presented a computational study of defect and optical properties in 220 [25] 215 [27] 214.0(t) [22] 214.1(e) [22] 253.4 [29] 254 [27] 253 [28] 250.5(t) [22] 250.5(e) [22] 273.6 [28] 276.6 [25] 275 [27] 273.6 [28] 270.9(t) [22] 271.0(e) [22] 343.4 [28] 333.5(t) [22] 333.0(e) [22] 1 S 0 → 3 P 0 383.8 382.6(t) [22] 382.6(e) [22] 1 S 0 → 1 I 6 390.8 402 [29] 404 [25] 403 [26] 402(e) [27] 406.3(e) [28] 390.8(t) [22] 390.9(e) [22] 1 S 0 → 3 P 1 392.4 392.9(t) [22] 392.9(e) [22] 1 S 0 → 1 I 6 395.0 396.0(t) [22] 395.5(e) [22] 1 S 0 → 3 P 2 412.9 411.6(t) [22] 411.3(e) [22] …”
Section: Resultsmentioning
confidence: 99%
“…2(a, b)). This may be explained by the higher efficiency of Pr 3+ 3 P 0 population via the energy transfer from excitonic states or recombination of Pr 3+ with electron-hole pairs [18,19]. A broad band within 300-550 nm arises in the emission spectrum of LiLuF 4 :Pr(0.1 mol%) upon the excitation at 8.86 eV (Fig.…”
Section: Resultsmentioning
confidence: 99%